User Sentiment Analysis X Towards Makan Bergizi Gratis Program Using Automatic Labeling Technique with Deepseek AI - Julianto, Indri Tri; Nurpajar, Dini Siti (Aliansi Peneliti Informatika, 2025)
Public perception of national nutrition initiatives is instrumental in shaping inclusive and data-driven policy development. In Indonesia, the